DOMESTIC VIOLENCE DURING THE COVID-19 PANDEMIC: Study on Magdelene.co Articles - Ndruru, Greta Theresia; Dedees, Adek Risma (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2020)
The National Commission on Violence against Women (Komnas Perempuan) reports that there has been an increase in Domestic Violence (KDRT) during Large-Scale Social Restrictions (PSBB). The results of an online survey conducted by Komnas Perempuan led Magdalene.co to raise violence through the Safe Space channel specifically. Magdalene.co is a feminist online media that actively raises issues of gender and feminism. This study discusses what types of violence occur during the pandemic and how Magdalene.co raises domestic violence. This study uses a qualitative approach by conducting online observations of articles on the Safe Space channel presented during June 2020. This study also conducted interviews with the co-founder and reporter of Magdalene.co.  The results found that economic and psychological violence were the two types of violence that increased. These phenomena are due to the uncertain economic conditions during the pandemic. This research also found several efforts made by Magdalene.co in raising the issue of violence during the Covid-19 pandemic, one of which was by using a particular Safe Space channel. Launched June 2020, this channel collaborates with other institutions such as Komnas Perempuan and the "Apik" Legal Aid Institute. To cite this article (7th APA style):Nduru, G. T. & Dedees, A. R. (2020). Domestic Violence during the Covid-19 Pandemic: Study on Magdelene.co Articles. Journal Communication Spectrum: Capturing New Perspectives in Communication, 10(2), 83-93. http://dx.doi.org/10.36782/jcs.v10i2.2100